QUALITY ATTRIBUTES OF COOKIES PRODUCED FROM COMPOSITE FLOURS OF WHEAT, GERMINATED FINGER MILLET FLOUR AND AFRICAN YAM BEAN - V.F, Abioye; S.J, Olatunde; G, Elias (International Journal of Research -GRANTHAALAYAH, 2018)
Cookies are ready to eat convenient food for all ages and the consumption is on the increase in Nigeria due to urbanization which has led to increase in wheat importation. In order to reduce the effects of wheat importation on the economy, this study looked into the use of locally grown crops for production of cookies. Cookie samples were produced from blends of wheat flour, germinated finger millet and African yam bean. Different proportions of flour blends were obtained using design experts. The flour mixes were evaluated for the proximate, minerals composition, antinutrients and the functional properties while the sensory properties of the cookies were determined. The proximate composition of the composite flour varied from 12.20-12.54; 8.89-10.62; 1.31-1.65; 1.13-1.39; 1.82-1.48 and 74.33-72.66% for moisture, protein, fat, crude fibre, ash and carbohydrate content of the flour, respectively. The mineral content of the flour ranged from 9.064-9.10, 0.29- 0.32, 0.42-0.45, 0.24-0.28% for calcium, phosphorus, potassium and sodium, respectively. The anti-nutritional properties of the flour ranged from 0.0074 to 0.0098%, 0.1700 to 0.1990%, 0.0905 to 0.1080% and 1.2500 to 1.4900%, for tannin, phytate, oxalate and trysin inhibitor, respectively. The functional properties of the composite flour ranged from 0.66-0.67 g/ml; 25.87- 27.48 g/ml; 6.11-8.12 g/ml; 0.75- 0.83 g/ml; 106.65 to 124; 91.70-99.75 g/100g; for bulk density, water absorption capacity, oil water capacity, foaming capacity and foaming solubility, respectively. The sensory attributes studied were colour, taste, texture and crispness. This study has shown that there was a notable improvement on the nutritional and functional properties of the flour while there was reduction in the ant nutrients.